Mojo workin': the old African American Hoodoo system - Hazzard-Donald, Katrina (University of Illinois Press, 2013)
Prescript -- Traditional religion in West Africa and in the new world: a thematic overview -- Disruptive intersection: slavery and the African background in the making of Hoodoo -- The search for High John the Conquer -- Crisis at the crossroads: sustaining and transforming Hoodoo's old black tradition from Emancipation to World War II -- The demise of Dr. Buzzard: black belt Hoodoo between the two World Wars -- Healin' da sick, raisin' da daid: Hoodoo as health care, root doctors, midwives, treaters -- Black belt Hoodoo in the post-World War II cultural environment -- Postscript